THU0135 The course of lower extremity function in patients with early rheumatoid arthritis over the first five years. (15th June 2017) - Bengtsson, M Mellblom; Book, C; Hagel, S; Jacobsson, LT; Turesson, C
Abstract : Background: Rheumatoid arthritis (RA) frequently involves joints of the feet and the knees. Disability related to arthritis in the lower extremities has a major impact in many patients, but has not been extensively studied. Objectives: To investigate lower extremity function in early RA, using validated tests, and to assess its relation to other disease parameters. Methods: Consecutive patients with early RA (symptom duration ≤12 months) in an inception cohort from a well-defined area were followed according to a structured protocol, with visits at inclusion and after 1, 2 and 5 years. Lower extremity function was investigated using the Index of Muscle Function (IMF) (1), a validated battery of tests by which the patient's general ability, muscle strength, muscular endurance and balance/coordination are assessed by a physiotherapist. The scores on the subscales are added for a total IMF score (IMF total) of 0–40. A subscore of the Health Assessment Questionnaire Disability Index (HAQ-DI), based on the 10 questions that are mainly dependent on function of the lower extremities (the HAQ-DI-LE (2)) was calculated, as well as a modified HAQ-DI-LE (mHAQ-DI-LE) that included only the three HAQ-DI domains in which all questions relate mainly to the lower extremities. Changes in the IMF total score and subtest scores between visits were analyzed using the Wilcoxon signed rank test. Correlations between disease parameters were assessed using Spearman's rank test. Results: A total of 106 patients (67% women, mean age 61 years, mean baseline DAS28 4.4, median baseline HAQ-DI 0.75) were included. Data on IMF total were available for 100, 89 and 67 patients at the 1, 2 and 5-year visits. Lower extremity function improved from baseline to the 1-year visit (IMF total median 10; interquartile range (IQR) 4–16 vs. 7; IQR 3–12) (p=0.01). This was followed by a decline in lower extremity function, in particular between the 2-year and 5-year visits (IMF total median 8 (IQR 3–13) vs 9.5 (IQR 3.75–18.25); p=0.001). This was mainly due to worsening in test results for muscle strength (median 4 (IQR 1–6) vs 5 (IQR 2–9); p=0.001) and for balance/coordination (median 2 (IQR 0–4) vs 3 (IQR 2–6); p=0.001). At baseline, IMF total correlated with HAQ-DI-LE (r=0.46), mHAQ-DI-LE (r=0.49) and HAQ-DI (r=0.40) (all p<0.001), whereas there were weaker correlations with CRP (r=0.24; p=0.02) and DAS28 (r=0.28; p=0.004). There were consistent correlations between IMF total and HAQ-DI-LE, mHAQ-DI-LE and HAQ-DI at all time points, but no significant correlations for IMF total with CRP and DAS28 at the 2-year visit. Conclusions: In early RA, there was improvement in lower extremity function during the first year, followed by a gradual decline, possibly explained by lack of complete disease control and aging. Tests of muscular function in the lower extremities may reveal aspects of RA disease severity that are not fully captured by standard disease activity measures, and may add important information regarding functional loss. References: Ekdahl et al. Advances in Physiotherapy 1999; 1: 45–55. Ekdahl et al. J Clin Epidemiol 1989; 42: 947–54. Disclosure of Interest: None declared